Environmental Turbulence and Strategic Aggressiveness in Sport Businesses During the Period of Economic Crisis - Kriemadis, Thanos; Kariofyllas, Charalampos; Melanthiou, Yioula; Kartakoullis, Nikos; Sakas, Damianos P. (My University, 2021)
The present study aims at examining the alignment between environmental turbulence and strategic aggressiveness in sport businesses during a period of economic crisis. A questionnaire-based research with the participation of 161 senior and top-ranking members of sport businesses has been carried out. The instrument was based on modification of Ansoffskampsk#x2019;s instrument for measuring the variables in the Strategic Success Hypothesis (SSH). An alignment of environmental turbulence and strategic aggressiveness in sport businesses during the period of economic crisis was ascertained. This fact indicates that sport businesses apprehend the level of environmental turbulence in which they venture and consequently react promptly, which is shown by the strategic aggressiveness they shape.
Keywords: Strategic planning; Environmental turbulence; Strategic aggressiveness; Economic crisis; Sport businesses